PERCEIVED EASE AND SECURITY OF USING QRIS TOWARDS CASHLESS SOCIETY - Gideon Setyo Budiwitjacksono; Ahmad Septa (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: The purpose of the research journal is to investigate the perceptions of accounting students at UPN